2014
DOI: 10.1186/1756-0500-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine administration does not alter salivary α-amylase activity in young male daily caffeine consumers

Abstract: BackgroundTo follow up on a recent report from our lab [Hum Psychopharmacol 25:359–367, 2010.] we examined the effects of caffeine on salivary α-amylase (sAA) activity in response to an engaging, non-stressful task in healthy young males (age 18–30 yrs) who consumed caffeine on a daily basis. Using a placebo-controlled, double-blind, between-subjects design, 45 men received either placebo, 200 mg or 400 mg of caffeine (Vivarin®). Participants then rested for 20 minutes, and performed a 20-minute computerized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Furthermore, another study showed that caffeine intake, was the only statistically significant predictor of higher sAA levels among nurses at a paediatric intensive care unit [ 67 ]. Contrary to our findings, another study showed that caffeine intake in combination with an engaging non-stressful task did not affect sAA activity in healthy young male daily caffeine consumers [ 35 ]. However, due to the limited available literature, it is difficult to explain our sAA findings in regards to the sAA response to different coffee types.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, another study showed that caffeine intake, was the only statistically significant predictor of higher sAA levels among nurses at a paediatric intensive care unit [ 67 ]. Contrary to our findings, another study showed that caffeine intake in combination with an engaging non-stressful task did not affect sAA activity in healthy young male daily caffeine consumers [ 35 ]. However, due to the limited available literature, it is difficult to explain our sAA findings in regards to the sAA response to different coffee types.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found that coffee consumption significantly increased BP, within the healthy physiological levels, in a gender specific manner in normotensive healthy individuals 3 h post-consumption, without differences between coffee types; which may be partially explained by SNS activation. Our results are in agreement with studies showing a temporary hypertensive coffee effect [ 35 , 64 , 68 70 ], even after small doses of consumed caffeine (80 mg/day) [ 31 ]. However, other studies have shown that the type of coffee may have a different impact on BP suggesting that boiled coffee may cause a higher increase in BP compared to filtered coffee, whereas instant coffee and decaf do not affect BP, after daily consumption of large coffee doses (>5 cups) for several days and/or weeks [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In literature, there are described factors that might modify the concentrations of cortisol and activity of alpha-amylase in saliva, such as the age, sex, use of oral contraceptives, menstrual cycle,[ 30 38 ] cycles of dream, and consumption of caffeine[ 39 ] and nicotine. [ 40 ] These factors were not controlled or used as criteria of exclusion because our sample size was very limited.…”
Section: Discussionmentioning
confidence: 99%